A comparative taxonomic study of nutlets of Stachys L. in Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
Nutlets of 22 taxa of Stachys (13 species and seven subspecies and two varieties), representing seven of the currently recognized sections distributed in northern Iraq were examined by light microscope. The basic shape of nutlets in most taxa studied is Obovoid, but Oblong also found in S.megalodanta Hausskn.& Bornm. ex P.H.Davis, S.setirefa C.A.Mey. subsp daenensis (Gandog.) Rech.f.and S. kurdica Boiss.& Hohen. var.kurdica, while the Subgloboid shape found in S. iberica M.Bieb. and S. inflata Benth., more over the Broad triangular shape was found in S. nephrophylla Rech.f. and S.lanigera (Bornm.) Rech.f.., the biggest size of nutlets was found in S.inflata L. and the smallest was in S.melampyroides Hand.-Mzt. Regarding sculpturing pattern of nutlet surface six basic types can be distinguishe and the reticulate type was the most common among the studied taxa, while the Foveate type appeared only in S. lavandulifolia Vahl.Symb. The type of sculpturing and the shape of nutlets are more useful than the size values, because there were convergence in the size values of the nutlets between species, it is seems that the type of the shape is useful in separating sections, rather than separating species within the same section, and the type of sculpturing is almost useful in separating between species within the same section.